2017
DOI: 10.1017/ice.2017.100
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Tuberculosis Cases Among Healthcare Workers to Inform Infection Control Policy and Practices

Abstract: OBJECTIVE To determine the number and proportion of healthcare worker (HCW) tuberculosis (TB) cases infected while working in healthcare institutions in the Netherlands and to learn from circumstances that led to these infections. DESIGN Cohort analysis. METHODS We included all HCW TB patients reported to the Netherlands TB Register from 2000 to 2015. Using data from this register, including DNA fingerprints of the bacteria profile and additional information from public health clinics, HCW TB cases were classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…It is more reasonable to measure occupational exposure at HCFs with indicators of AR and AR% using teachers as non-occupational exposure group due to the similar socioeconomic status in Henan. Additionally, one study based on DNA fingerprints of the bacteria profile reported that 24% of HCW TB cases were infected during work in a setting with a low incidence of TB, which was lower than this present study [ 20 ].…”
Section: Discussioncontrasting
confidence: 80%
“…It is more reasonable to measure occupational exposure at HCFs with indicators of AR and AR% using teachers as non-occupational exposure group due to the similar socioeconomic status in Henan. Additionally, one study based on DNA fingerprints of the bacteria profile reported that 24% of HCW TB cases were infected during work in a setting with a low incidence of TB, which was lower than this present study [ 20 ].…”
Section: Discussioncontrasting
confidence: 80%
“…Subsequent involvement to latent TB and the emergence of the resistance of strains may be a diagnostic problem in healthcare staff and medical students [4,5]. Infected individuals may present mild or nonspecific symptoms and signs and lead to either failure or delayed diagnosis of TB [6]. The prevalence of undiagnosed TB was estimated to be 67% infected cases after death [7].…”
Section: Introductionmentioning
confidence: 99%